Development of an ANN optimized mucoadhesive buccal tablet containing flurbiprofen and lidocaine for dental pain - Hussain Amjad; Syed Muhammad Ali; Abbas Nasir; Hanif Sana; Arshad Muhammad Sohail; Bukhari Nadeem Irfan; Hussain Khalid; Akhlaq Muhammad; Ahmad Zeeshan (Acta Pharmaceutica)
A novel mucoadhesive buccal tablet containing flurbiprofen (FLB) and lidocaine HCl (LID) was prepared to relieve dental pain. Tablet formulations (F1-F9) were prepared using variable quantities of mucoadhesive agents, hydroxypropyl methyl cellulose (HPMC) and sodium alginate (SA). The formulations were evaluated for their physicochemical properties, mucoadhesive strength and mucoadhesion time, swellability index and in vitro release of active agents. Release of both drugs depended on the relative ratio of HPMC:SA. However, mucoadhesive strength and mucoadhesion time were better in formulations, containing higher proportions of HPMC compared to SA. An artificial neural network (ANN) approach was applied to optimise formulations based on known effective parameters (i.e., mucoadhesive strength, mucoadhesion time and drug release), which proved valuable. This study indicates that an effective buccal tablet formulation of flurbiprofen and lidocaine can be prepared via an optimized ANN approach.